(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the socio-political movements in Karakalpakstan during the early 20th century, analyzing the region’s historical dynamics through independent voices and printed sources of the period. Drawing upon local newspapers, memoirs, and political documents, the study highlights how Karakalpak intellectuals responded to colonial rule, social inequality, and national awakening. The article demonstrates that early Karakalpak activism was closely linked to broader regional reformist currents, particularly Jadidism, and played a significant role in shaping the region’s identity and resistance narratives.